Pattern of current tobacco use in a rural block of North India - Jangra, Anuj; Malik, J. S.; Singh, Srishti; Sharma, Nitika (International Journal Of Community Medicine And Public Health, 2017)
Background: Tobacco is the only legal drug that kills many of its users when used exactly as intended by manufacturers. WHO has estimated that tobacco use (smoking and smokeless) is currently responsible for the death of about six million people across the world each year. Although often associated with ill-health, disability and death from non-communicable chronic diseases, tobacco smoking is also associated with an increased risk of death from communicable diseases. This study was conducted with aim to observe the current pattern of tobacco use in a rural block of north India. Methods: The study was conducted in Lakhanmajra block (rural) of Haryana, India, in year 2015-2016 among 1000 study subjects aged 15-64 years selected by systematic random sampling technique. Results: The overall prevalence of current tobacco-smoking use to be 12.8% and it was higher among males (11.2%) as compared to females (3.2%). The median age for initiation of smoking tobacco was 18 years, smokeless tobacco was 20 years. Conclusions: Our study stresses is the need to have rural orientation in the National Tobacco Control Programme since the poorly educated individuals living in rural areas are at the maximum risk of using tobacco, identifying ways and means of reaching out to these communities will be critical to the success or failure of the program.